2020
DOI: 10.1073/pnas.2002278117
|View full text |Cite
|
Sign up to set email alerts
|

DROOPY LEAF1 controls leaf architecture by orchestrating early brassinosteroid signaling

Abstract: Leaf architecture directly determines canopy structure, and thus, grain yield in crops. Leaf droopiness is an agronomic trait primarily affecting the cereal leaf architecture but the genetic basis and underlying molecular mechanism of this trait remain unclear. Here, we report that DROOPY LEAF1 (DPY1), an LRR receptor-like kinase, plays a crucial role in determining leaf droopiness by controlling the brassinosteroid (BR) signaling output in Setaria, an emerging model for Panicoideae grasses. Loss-of-function m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…At the 4-leaf stage, SiBRI1-OX seedlings in two independent lines, OX23 and OX14 , had larger leaf angles and droopier leaves than Ci846 seedlings (Fig. 5 A); notably, large leaf angles and drooping leaves have been reported to be specific phenotypes controlled by BR in foxtail millet [ 25 ]. Both of these phenotypes were dependent on the protein expression level of SiBRI1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the 4-leaf stage, SiBRI1-OX seedlings in two independent lines, OX23 and OX14 , had larger leaf angles and droopier leaves than Ci846 seedlings (Fig. 5 A); notably, large leaf angles and drooping leaves have been reported to be specific phenotypes controlled by BR in foxtail millet [ 25 ]. Both of these phenotypes were dependent on the protein expression level of SiBRI1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the functional conservation of BRI1 among different species. Previous work has demonstrated that DROOPY LEAF1 (DPY1) participates in BR signaling and inhibits the interaction between SiBRI1 and SiBAK1 [ 25 ], but SiBRI1 in foxtail millet has not yet been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Due to our continuing efforts, positional cloning in Setaria is now practicable using “SSR41” and “Yugu1” EMS mutants as plant materials. To date, map-based cloning has been used to characterize at least eight S. italica genes, including SiMADS34 ( Hussin et al, 2021 ), DPY1 ( Zhao et al, 2020 ), SiSTL1 ( Tang et al, 2019 ), SiSTL2 ( Zhang et al, 2018a ), SiYGL1 ( Li et al, 2016 ), SiYGL2 ( Zhang et al, 2018b ), Loose Panicle1 ( Xiang et al, 2017 ), and SiAGO1b ( Liu et al, 2016 ). These studies illustrate that “SSR41” and “Yugu1” are suitable germplasm resources for forward genetics and positional cloning research on Setaria .…”
Section: Discussionmentioning
confidence: 99%
“…We propose that “SSR41” is an ideal genotype to match to “Yugu1” mutants to construct mapping populations, because “SSR41” is morphologically similar to, but highly genetically divergent from, “Yugu1”. To data, several genes of S. italica have been cloned using “SSR41” and the corresponding “Yugu1” mutant, including DPY1 ( Zhao et al, 2020 ), SiAGL1b ( Liu et al, 2016 ), SiSTL1 ( Tang et al, 2019 ), SiSTL2 ( Zhang et al, 2018a ), SiYGL1 ( Li et al, 2016 ), and SiYGL2 ( Zhang et al, 2018b ). In addition, “SSR41” is an elite cultivar with high yields, good grain quality, resistance to diverse diseases, and wide local adaptability, so it will be useful for breeding and crop improvement.…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that a decellularized leaf scaffold can be loaded with polylactic-co-glycolic acid (PLGA)-based rapamycin nanoparticles, these nanoparticle-perfused leaves could inhibit venous neointimal hyperplasia in a rat inferior vena cava (IVC) venoplasty model at day 14; decellularized onion cellulose can also be coated with PLGA rapamycin nanoparticles and inhibit venous neointimal hyperplasia (Bai et al, 2021a). Plant leaf has a very specific architecture, including leaf stem, leaf midrib, vascular system, vein, and cuticle (Fan et al, 2019;Zhao et al, 2020). This system is important for water and nutrient transportation and storage.…”
Section: Introductionmentioning
confidence: 99%